2020
DOI: 10.3390/ijerph17249248
|View full text |Cite
|
Sign up to set email alerts
|

International Prevalence and Correlates of Psychological Stress during the Global COVID-19 Pandemic

Abstract: This study reports perceived stress and associated sociodemographic factors from an international sample of adults, during the COVID-19 pandemic. The Perceived Stress Scale (PSS-10) along with socio-demographic questions were conducted between 8 April 2020 and 11 May 2020. The survey was translated from English into five languages. Recruitment was conducted worldwide using social media. A total of 1685 survey responses were collected across 57 countries with eleven countries (≥30 responses/country) included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
71
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 35 publications
13
71
3
3
Order By: Relevance
“…These findings are consistent with previous studies, where older adults with these characteristics may experience greater fear of being infected or dying themselves, leading to higher depression levels [32,37,38]. In line with previous evidence in Chinese adolescents and adults, the findings showed that older adults who had higher education levels and higher household income might be less influenced by the COVID-19 pandemic, indicating a comparative lower depression level [5,22]. The discrepancy with previous evi-dence occurred in the indicator of occupational status [23,24], where no significant difference was found in the current study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are consistent with previous studies, where older adults with these characteristics may experience greater fear of being infected or dying themselves, leading to higher depression levels [32,37,38]. In line with previous evidence in Chinese adolescents and adults, the findings showed that older adults who had higher education levels and higher household income might be less influenced by the COVID-19 pandemic, indicating a comparative lower depression level [5,22]. The discrepancy with previous evi-dence occurred in the indicator of occupational status [23,24], where no significant difference was found in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the demographic and behavioral factors identified in the present study only explained 15% of the variance of depression levels, so other factors need to be investigated in future studies. In addition, the depression levels did not significantly differ in gender, whereas other studies have found a prominent role for the gender variable in the psychological responses towards the pandemic [21,22]. This point deserves further investigation.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The downside is that it tends to get worse and no one is completely resistant to stress. An increasing number of people exposed to stress and the contraindications associated with stress show us that there is a need for equipment and methodology that would help detect stress and fluctuations in mental health and help reduce them [ 19 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The stress is affecting also the economy, and U.S. employers are spending health care and working days at $300 billion a year.…”
Section: Human Stress Phenomenamentioning
confidence: 99%